The Main Features of Medical Terms in English - Maxmudova Gulchehra (Scientific Trends, 2023)
Terminology is the brain of all areas. In particular, it is impossible to imagine the medical field without terms. This article discusses the linguistic features, specificity, translation mechanism of terms used in English and Uzbek languages.
Keywords: Terminology, term, linguistics, translation, feature, mechanism, abbreviation.